Analysis of Physical Distribution of Sediment at Sembrong Reservoir Using GRADISTAT - Hashim, SINS; TAlib, SHA; Abustan, MS (International Journal of Engineering and Technology, 2018)
Sembrong reservoir is a flood-control reservoir which is managed by Syarikat Air Johor since 1984. The reservoir provides clean water supply to 240,000 consumers in the district of Kluang and some parts of Batu Pahat. Reservoir storage is often affected by sedimentation due to soil erosion in the catchment area. As the sediments accumulate, the reservoir gradually loses its ability to store water for the purposes for which it was built. This research is initiated to characterize the sediment which could be used as control in future research in the treatment of contaminated sediment. The objective of this study was to determine the distribution of sediment at Sembrong Reservoir. In this experiment, sediment sampling was done using gravity corer at 6 different points throughout the reservoir. In addition, the physical properties of sediment is investigated by conducted experiments include scanning electron microscope (SEM) and particle size distribution The analysis of sediment distribution was done using GRADISTAT. Results obtained from the analysis shows that the particle in Sembrong reservoir were classified as very coarse sand and sandy gravel.